Saponin components in Polygala tenuifolia as potential candidate drugs for treating dementia - Li, Songzhe; Hou, Zhitao; Ye, Ting; Song, Xiaochen; Hu, Xinying; Chen, Jing (Frontiers in Pharmacology, 2024)
Objective: This study aims to elucidate the intervention effects of saponin components from Polygala tenuifolia Willd. (Polygalaceae) on dementia, providing experimental evidence and new insights for the research and application of saponins in the field of dementia.This review is based on a search of the PubMed, NCBI, and Google Scholar databases from their inception to May 13, 2024, using terms such as "Polygala tenuifolia," "Polygala tenuifolia and saponins," "toxicity," "dementia," "Alzheimer's disease," "Parkinson's disease dementia," and "vascular dementia." The article summarizes the saponin components of Polygala tenuifolia, including tenuigenin, tenuifolin, polygalasaponins XXXII, and onjisaponin B, as well as the pathophysiological mechanisms of dementia. Importantly, it highlights the potential mechanisms by which the active components of Polygala tenuifolia prevent and treat diseases and relevant clinical studies. Results: The saponin components of Polygala tenuifolia can reduce β-amyloid accumulation, exhibit antioxidant effects, regulate neurotransmitters, improve synaptic function, possess anti-inflammatory properties, inhibit neuronal apoptosis, and modulate autophagy. Therefore, Polygala tenuifolia may play a role in the prevention and treatment of dementia. Conclusion: The saponin components of Polygala tenuifolia have shown certain therapeutic effects on dementia. They can prevent and treat dementia through various mechanisms.